Energy Production Analysis of Photovoltaic Shading Devices (PVSD) in Integrated Façade Systems (IFS) - Ibraheem, Yahya; Piroozfar, Poorang; Farr, Eric R. P.; Ravenscroft, Neil (Frontiers in Built Environment, 2020)
The need for more responsive built environment in the age of climate change has led building professionals to resort to integrated design solutions where a combination of different technologies is utilised to improve what traditionally the tectonics of a building were expected to fulfil rather independently. One of such solutions are Integrated Façade Systems (IFS), which deploy different technologies in or related to building façades to improve building performance. To measure the efficiency of such solutions, three broad categories of methods are in use, namely real, scaled or mock physical models, mathematical models and simulations of which the latter is the most time- and cost-efficient and depending on the platform can provide the most user-friendly method. The flexibility, ease of use and broader coverage of Building Energy Simulation (BES) tools make them a more viable alternative. Developing a benchmark or a base-case model against which the impact of parametric changes of the IFS can be measured is the first step in BES and bares high importance on methodological reliability and validity of the results. This paper uses a specially devised methodology to develop a base-case model for BES of highly- to fully-glazed office buildings in hot and arid climates. BES results of the energy production of the base-case and over 1600 parametric combinations of the model’s system and sub-system levels variables have been used to perform a sensitivity analysis to test the robustness of the results. The results presented in this paper form the last phase of a three-phased analysis of a comprehensive research, designed to provide a full account of how different combinations of a set of variables can and will influence energy performance of highly- to fully-glazed office buildings in hot and arid climates.